The University of California, Irvine (UCI) School of Medicine is seeking an outstanding Endowed Chair of Medical Humanities and Arts - Pearlman, Rachel (Research and Humanities in Medical Education, 2020)
About the Program in Medical Humanities and Arts The Program in Medical Humanities and Arts, which has garnered national and international recognition, began informally as a medical student elective and was recognized as an official program in 2000. Program goals are to expose and engage medical students in humanities and the arts to help them develop critical thinking skills and empathy to understand their patients' illness experiences. The study of medical humanities enables students to: build effective relationships with patients, family members and health professional team members; enhance their well-being and self-care; understand the influence of social, cultural and economic determinants of health; and appreciate the potential of physicians to serve as advocates for health equity. (https://www.meded.uci.edu/student-life/medical-humanities.asp) Successful applicants will demonstrate an exemplary track-record of program development, teaching, and academic scholarship in medical humanities. We are seeking applicants recognized at national or international levels. A background in health/medical humanities, and experience teaching and working in a medical school or academic health setting is highly desirable. Applicants should be capable of leading and expanding current programs. They must have an MD, PhD or equivalent. They are expected to be qualified for a tenured position at the associate or full professor level. The faculty member's appointment will be in the most appropriate department home, with potential for joint appointment in a school and/or department which compliments the successful candidate's particular focus. Responsibilities: Develop, design and teach curriculum in medical humanities in undergraduate medical education (medical student), graduate (residency), and faculty development programs Conduct research and scholarship Pursue grant writing, philanthropy, and fundraising to expand the program Collaborate with faculty from the College of Health Sciences including the Schools of Medicine, Nursing, Pharmacy and Population Health, the Director of Bioethics, and faculty from relevant UCI campus units such as the Center for Medical Humanities, School of Humanities and School of the Arts, to develop interdisciplinary education and research Participate in local, national and international medical humanities associations and organizations Promote scholarship by facilitating medical student research in medical humanities Serve as faculty advisor to oversee production of student works including the Plexus journal and Project Hx (http://www.meded.uci.edu/student-life/med-humanities-plexus.asp). Oversee and coordinate medical students' awards including Graduation with Distinction in the Humanities/Arts and the Office of Medical Education Award in Humanities/Arts Develop and expand a UCI-SOM website describing offerings, scholarship, and activities of the Program in Medical Humanities/Arts Application materials should include a curriculum vitae, a one-page letter of interest, a statement of research, a reflective teaching statement, and a separate statement that addresses past and potential contributions to diversity, equity and inclusion. Applicants may complete an online application profile and upload their CV and application materials electronically. The University of California is committed to creating and maintaining a community dedicated to the advancement, application, and transmission of knowledge and creative endeavors through academic excellence, where all individuals who participate in University programs and activities can work and learn together in a safe and secure environment, free of violence, harassment, discrimination, exploitation, or intimidation. With this commitment as well as a commitment to addressing all forms of academic misconduct, UC Irvine conducts institutional reference checks for candidates finalists to whom the department or other hiring unit would like to extend a formal offer of appointment into Ladder Rank Professor or Professor of Teaching series, at all ranks (i.e., assistant, associate, and full). The institutional reference checks involve contacting the administration of the applicant's previous institution(s) to ask whether there have been substantiated findings of misconduct that would violate the University's Faculty Code of Conduct. To implement this process, UC Irvine requires all candidates of Ladder Rank Professor or Professor of Teaching series, at all ranks (i.e., assistant, associate, and full) to complete, sign, and upload the form entitled "Authorization to Release Information" into AP RECRUIT as part of their application. If the candidate does not include the signed authorization to release information with the application materials, the application will be considered incomplete. As with any incomplete application, the application will not receive further consideration. Although all applicants for faculty recruitments must complete the entire application, only finalists (i.e., those to whom the department or other hiring unit would like to extend a formal offer) considered for Ladder Rank Professor or Professor of Teaching series, at all ranks (i.e., assistant, associate, and full) positions will be subject to institutional reference checks. Application review will begin immediately and continue until the position is filled. UCI is an Equal Opportunity/Affirmative Action Employer advancing inclusive excellence. All qualified applicants will receive consideration for employment without regard to race, color, religion, sex, sexual orientation, gender identity, national origin, disability, age, protected veteran status, or other protected categories covered by the UC nondiscrimination policy. A recipient of an NSF ADVANCE award for gender equity, UCI is responsive to the needs of dual career couples, supports work-life balance through an array of family-friendly policies, and is dedicated to broadening participation in higher education.